Cross-cultural design : 8th International Conference, CCD 2016, Held as Part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016 : Proceedings /: 8th International Conference, CCD 2016, Held as Part of HCI International 2016, Toronto, ON, Canada, July 17-22, 2016 : Proceedings. ([2016]) - Unknown
No abstract available